Generación de biohidrógeno por un proceso de biofotólisis directa utilizando un cultivo mixto de microalgas (2010)
It was developed a process of Direct Biophotolysis for the Biohydrogen production using mixed cultures of non-axenic green microalgae generated from samples taken at the Wetland Santa Maria del Lago (Bogota, Colombia). The substrate for the cultivation of microalgae was the organic matter contained in the original matrix in the natural environment. It was possible to generate a volume of 8.5 ml of hydrogen gas from concentrated volumes of microalgae of 250 ml in two samples of wáter in the wetland. The maximum convertion percentage obtained was low, a result consistent with the literature referenced in the production of hydrogen from this process. However, there are interesting problems in the generation of this energy source and technology development at the national level.